Disharmony Between National and Regional Policies in Maritime Governance: A Case Study of Tanjungpinang City Port - Merrisa Rani; Ibaniyah Ibaniyah; Ririn Murtiani (Journal of Maritime Policy Science, 2026)
This study examines the disharmony between national and regional policies in maritime governance at Tanjungpinang City Port. The issue emerges from the tension between centralized maritime regulation, which emphasizes port safety, operational standards, and national connectivity, and regional governance needs related to urban mobility, spatial planning, public services, and local economic development. The purpose of this study is to analyze how policy misalignment affects port governance and to identify the institutional, regulatory, and spatial challenges that shape the relationship between national authority and regional responsiveness. This research uses a qualitative case study approach supported by document analysis, stakeholder-based qualitative data, and descriptive policy analysis. The data were obtained from national maritime regulations, regional planning documents, institutional reports, field observations, and relevant stakeholder perspectives. The findings show that policy disharmony produces institutional fragmentation, regulatory misalignment, weak port-city spatial integration, limited stakeholder coordination, and gaps in public service planning. These conditions reduce the effectiveness of port management and limit the capacity of Tanjungpinang City Port to support sustainable regional development. The study concludes that maritime governance reform requires an adaptive and integrated framework that connects national standards with regional priorities through policy harmonization, institutional coordination, stakeholder participation, digital governance, and port-city spatial integration. Such reform is necessary to strengthen accountability, improve public services, and position Tanjungpinang City Port as a strategic node for inclusive and sustainable maritime development.